Critical race theory and the question of safety in dialogues on race - Conradie, Marthinus Stander (Acta theologica, 2016)
This study seeks to combine research from critical race theory, as applied to post-1994 South Africa, with insights from practical theology. It looks into points of agreement between these perspectives, especially the call to critically appraise ideologies that deny or obscure the present-day consequences of racism. On this foundation, the article moves on to consider the recommendations adduced by Leonardo and Porter (2010:147) and Sue (2013:666-669) as to how dialogues around race and racism can be enhanced. The article begins by contextualising its argument, followed by an overview of the guiding principles of CRT, focusing on the way these have been applied to research in South Africa. Thereafter, the precepts of CRT are matched with insights from scholars in theology regarding the continued need to glean more precisely nuanced understandings of how race plays out in South African society. Finally, the article draws from Leonardo and Porter (2010:140-142) and Sue’s (2013:666-669) suggestions.